Formulation and evaluation of dorzolamide hydrochloride-loaded nanoparticles as controlled release drug delivery system (Asian Journal of Pharmaceutics (AJP), 2014)
This study aimed to prepare anti-glaucomatous dorzolamide hydrochloride-(Dorzo) loaded nanoparticles as a controlled release system. Eudragit RS 100 (RS) and/or RL 100 (RL) were used in formulations by an opportunely adaptedQuasi-emulsion solvent diffusion technique. The formulations were evaluated in terms of particle size, zeta potential, drug entrapment, and release profile. All formulations showed tiny particle size varying from 114 to 395 nm for RS and65 to 277 nm for RL. Positive zeta potential was +19 to +32 mV for RS and +23 to +42 mV for RL formulations. It was demonstrated that increasing polymer concentration lead to increase the percentage of drug entrapped in all batches, toa certain extent (drug: polymer 1:4). Nanoparticles prepared using RL showed lower entrapment efficiency than RS. Incontrast, increasing the stirring rate resulted in an increase in the percentage of Dorzo entrapped. A prolonged drug release was shown by all the formulations. Increasing the polymer concentration caused a decrease in the release rate. Moreover, it was evident that increasing RL content increased the amount of Dorzo released. Dorzo-loaded nanoparticles could represent promising drug ophthalmic carriers, due to small particle size, positive zeta potential, and sustained release profile; hence, expecting prolonged corneal contact time, more therapeutically efficient, decreased frequency of administration per day,and better patient compliance.